2022
DOI: 10.1007/s10072-022-06247-w
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic correlation between mosaic variegated aneuploidy 1 (MVA1) and a novel BUB1B variant: a reappraisal of a severe syndrome

Abstract: Background The BUB 1 mitotic checkpoint serine/threonine kinase B (BUB1B) gene encodes a key protein in the mitotic spindle checkpoint, which acts as a surveillance mechanism, crucial for the maintenance of the correct chromosome number during cell deviation. Mutations of BUB1B gene are linked to mosaic variegated aneuploidy 1 (MVA1) syndrome, a rare autosomal recessive disorder characterized by widespread mosaic aneuploidies, involving different chromosomes and tissues. MVA1 is clinically charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A published case report giving the clinical history of an Italian girl with a karyotype showing 12% mosaics with a new variant of the BUB1B gene (c.2679 A > T, p.Arg893Ser). The girl was two years old and presented with severe neurological disorders, microcephaly and epileptic seizures [35]. Another case report involved a child who, at 6 months of age, showed severe developmental delay, microcephaly, hypotonia, intractable seizures including infantile spasms with hypsarrhythmia, and Dandy-Walker malformation on MRI.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…A published case report giving the clinical history of an Italian girl with a karyotype showing 12% mosaics with a new variant of the BUB1B gene (c.2679 A > T, p.Arg893Ser). The girl was two years old and presented with severe neurological disorders, microcephaly and epileptic seizures [35]. Another case report involved a child who, at 6 months of age, showed severe developmental delay, microcephaly, hypotonia, intractable seizures including infantile spasms with hypsarrhythmia, and Dandy-Walker malformation on MRI.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…A well-characterized MVA causative gene, Budding Uninhibited by Benzimidazole 1B (BUB1B) encodes the BUB-related 1 (BubR1) protein (Bolanos-Garci and Blundell, 2011). Previous work in mice found that a BubR1 hypomorphic allele substantially reduces protein level presenting with premature aging, and tumor formation, but not microcephaly (Baker et al, 2004;Hanks et al, 2004;Matsuura et al, 2006;Frio et al, 2010;Suijkerbuijk et al, 2010;Miyamoto et al, 2011;Baker et al, 2012;Wijshake et al, 2012;Choi et al, 2016;Yang et al, 2017;Pavone et al, 2022). Successful…”
Section: Introductionmentioning
confidence: 99%
“…Mosaic variegated aneuploidy (MVA) is a rare autosomal recessive disorder characterized by growth retardation, predisposition to cancer, and microcephaly (Garcia-Castillo et al, 2008;Suijkerbuijk et al, 2010;Bianchi et al, 2018;Pavone et al, 2022). Premature chromatid separation resulting in cells with numerically abnormal chromosomes (aneuploidy) is a hallmark feature of MVA.…”
Section: Introductionmentioning
confidence: 99%